2017
DOI: 10.11114/jets.v5i5.2131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Working Memory Training Targeting the Central Executive on Kindergarteners’ Numerical Skills

Abstract: Working memory capacities are associated with mathematical development. Many studies have tried to improve working memory abilities through training. Furthermore, the central executive has been shown to be the component of working memory, which is the most strongly related to numerical and arithmetical skills. Therefore, we developed a training program that specifically targeted the central executive to examine the possible impact on kindergarteners' working memory and numerical abilities. Thirty-four 5-6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…These results are in line with several studies which showed that it is possible to train WM in adults (E. Dahlin, Nyberg, Backman, & Neely, 2008;Olesen et al, 2004;Westerberg & Klingberg, 2007), in children (Bergman-Nutley & Klingberg, 2014;K. I. E. Dahlin, 2013;Dunning et al, 2013;Gray et al, 2012;Holmes et al, 2009;Klingberg et al, 2005;Klingberg et al, 2002;Van der Molen et al, 2010) as well as in preschoolers (Honoré & Noël, 2017;Kroesbergen et al, 2014;Passolunghi & Costa, 2016;Thorell et al, 2009). However, no effect was observed on the PL or the verbal CE; the effects were therefore restricted to the trained modality.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are in line with several studies which showed that it is possible to train WM in adults (E. Dahlin, Nyberg, Backman, & Neely, 2008;Olesen et al, 2004;Westerberg & Klingberg, 2007), in children (Bergman-Nutley & Klingberg, 2014;K. I. E. Dahlin, 2013;Dunning et al, 2013;Gray et al, 2012;Holmes et al, 2009;Klingberg et al, 2005;Klingberg et al, 2002;Van der Molen et al, 2010) as well as in preschoolers (Honoré & Noël, 2017;Kroesbergen et al, 2014;Passolunghi & Costa, 2016;Thorell et al, 2009). However, no effect was observed on the PL or the verbal CE; the effects were therefore restricted to the trained modality.…”
Section: Discussionsupporting
confidence: 92%
“…Then, the present study shows that improved visuo-spatial WM capacities have a very small impact on mathematics; it seems to help children in their current learning related to the VSSP, but this effect is very weak and there is no transfer effect to arithmetic. Therefore, according to the present findings together with those of our previous study (Honoré & Noël, 2017), it seems more effective to directly train specific numerical processes to impact numerical development. Indeed, WM training leads to improvement in counting skills only if a numerical material is used (Kroesbergen et al, 2014) and Kyttälä et al (2015) showed that training counting only, but not counting and WM abilities together, improves counting skills.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations